Methodological proposal for a semantic analysis of a symbolically generalized media - Díaz Herrera, Claudio (Revista General de Información y Documentación, 2020)
The article responds to a methodological problem that deepens the analysis of qualitative thematic content, unraveling the semantics of a symbolically generalized social science media. The proposal seeks to transform itself into a methodological contribution that complements bibliometric and co-word studies, which when presented through metric indicators, do not deepen in the semantic construction of these publications, being able to present a configuration as an area of study or scientific discipline. Through a bibliometric and relational work of Izquierdas journal, indicators with semantic value of this medium were methodologically studied. The complete trajectory of publications equivalent to 515 documents between the years 2008 and 2019 and extracted from the journal's website was analyzed. The procedure was carried out in two phases: the first one through the application of a qualitative thematic content analysis and; a second phase, where the results of this thematic categorization were analyzed, together with the key words and the published titles, in the understanding that these indicators contain core information that in analytical convergence end up constituting interpretative semantics of the media. The results show a methodological strategy capable of configuring a contained semantics as a symbolically generalized means of communication in the social sciences. On the other hand, the proposal has a potential for replication in other areas of study or scientific disciplines of the social and human sciences, due to its multi-paradigmatic epistemological nature.
Keywords: Symbolically generalized media; Semantic; Thematic content analysis; Thematic categorization; Qualitative; Social sciences